Peranan Penyuluh Pertanian Lapangan (PPL) sebagai Fasilitator dalam Penggunaan Metode Belajar Pendidikan Orang Dewasa (Andragogi) (Kasus di Gapoktan Madani, Desa Sampalan Klod, Kecamatan Dawan, Kabupaten Klungkung, Provinsi Bali) - HADI SURYO WIBOWO; NYOMAN SUTJIPTA; I WAYAN WINDIA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Role of Agricultural Field Extensionist (PPL) as a Facilitatorin Using Adult Learning Method (Andragogy), (Case in Gapoktan Madani,Sampalan Klod Village, Dawan Sub-district, Klungkung Regency,Bali Province) Agricultural extension acts as an agent for the change of farmers, which is byencouraging farmers to change their perceptions and behaviors to become farmerswith better ability and able to make their own decisions, which in turn will gain abetter life.The importance of the extensionist role and the importance of aninnovation conveyed by him, the extension agent should be able to become afacilitator who can foster and improve the ability of farmers in an effort to changelives for the better. This study aims to identify the role of the extension facilitators inusing adult education methods (andragogy). This research was conducted in acombination of farmer group (Gapoktan) Madani, Sampalan Klod Village, DawanSub-district, Klungkung Regency, Bali Province. The location of this study waschosen purposively or deliberately based on several considerations. The respondentcollected using census method in accordance with the number of active members ofthe farmer group as many as 60 people. This research uses the descriptive qualitativeanalysis method, which aims to give description and explanation about variablesstudied. Based on the results of the research, it is known that the role of agriculturalfield extension as a facilitator in the use of adult education learning method(andragogy) is included in the good category with the achievement score of 4.11.This means that the extension officer in Gapoktan Madani has been able to performhis role well as a facilitator in the use of adult education learning method(andragogy).